2021
DOI: 10.1177/21514593211011462
|View full text |Cite
|
Sign up to set email alerts
|

Octogenarian and Nonagenarians Are at a Higher Risk for Experiencing Adverse 30-Day Outcomes Following ORIF of Ankle Fractures

Abstract: Introduction: Despite an increasing number of elderly individuals undergoing surgical fixation for ankle fractures, few studies have investigated peri-operative outcomes and safety of surgery in an octogenarian and nonagenarian population (age >80 years). Materials and Methods: The 2012-2017 American College of Surgeons database was queried for patients undergoing open reduction internal fixation for isolated uni-malleolar, bi-malleolar and tri-malleolar ankle fractures. The study cohort was divided into 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The authors found that patients aged 80 years and above had a higher risk of wound complications, pulmonary complications, and renal complications within 30-days compared to their younger counterparts following ORIF for ankle fractures. 24 Therefore, it is critical to explore potential differences in postoperative morbidity and mortality within the hypertensive geriatric population following various orthopaedic surgeries, such as revision TKA (rTKA). Thus, the purpose of this study was to analyze whether there are any differences in risk for thirty-day morbidity and mortality following rTKA in hypertensive octogenarians (aged 80e89 years) compared to their younger hypertensive geriatric counterparts (aged 65e79 years).…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that patients aged 80 years and above had a higher risk of wound complications, pulmonary complications, and renal complications within 30-days compared to their younger counterparts following ORIF for ankle fractures. 24 Therefore, it is critical to explore potential differences in postoperative morbidity and mortality within the hypertensive geriatric population following various orthopaedic surgeries, such as revision TKA (rTKA). Thus, the purpose of this study was to analyze whether there are any differences in risk for thirty-day morbidity and mortality following rTKA in hypertensive octogenarians (aged 80e89 years) compared to their younger hypertensive geriatric counterparts (aged 65e79 years).…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of complications such as infection, nonunion, osteomyelitis, joint stiffness, and post-traumatic arthritis was still high. In 1999, Sirkin et [29]. Results of a retrospective study of patients with OTA/AO 43C tibial pilon fractures showed that increasing age (OR 1.02, P=0.040) was an independent predictor of deep infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al and Spek et alfound that age was an independent predictor of postoperative surgical site infection in ankle fracture patients [ 27 , 28 ]. A comparative study of 19,585 patients with ankle fractures showed that 30-day wound complications were significantly increased in individuals > 80 years (OR 1.84; P = 0.019) [ 29 ]. Results of a retrospective study of patients with OTA/AO 43C tibial pilon fractures showed that increasing age (OR 1.02, P = 0.040) was an independent predictor of deep infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%